PERMACULTURAL PLANNING OF THE OFAIÉ LAND LOCATED IN THE MUNICIPALITY OF BRASILAcirc;NDIA, MATO GROSSO DO SUL - De Calais, Mariana Perle [UNESP]; Mendes, Camila Pereira [UNESP]; Okimoto, Fernando Sergio [UNESP] (Univ Federal Ceara, Geography Posgraduate Program, 2024)
The present study aims to propose permacultural-based interventions in the Ofai & eacute; indigenous land, located in the municipality of Brasil & acirc;ndia/MS. Specific objectives include describing aspects of the physical geography of the Ofai & eacute; indigenous land in Brasil & acirc;ndia/MS, identifying land uses and occupations in the mentioned territory, and suggesting permacultural interventions in the study area. To achieve these objectives, this study relies on secondary sources, primarily existing literature on the Ofai & eacute; indigenous land in Brasil & acirc;ndia/MS. The proposed interventions are grounded in ethnic knowledge and the characteristics of the local geography, including hydrography, vegetation, soil, and topography, among others, identified in previous studies. It is believed that implementing the suggested permacultural interventions can significantly improve the quality of life for the community residing in the studied land and aid in recovering recently incorporated degraded soil areas into the territory of the Ofai & eacute; people. .
Keywords: Ofai & eacute; Indigenous lands; Permaculture